Knowledge and attitude towards hiv/aids among nursing students of college of nursing, jaffna - Nirushitha, L.; Thabotharan, D.; Sivapalan, K. (University of Jaffna, 2018)
HIV/AIDS is one of the major health outbreaks which causes mortality in global level more than 1.1 million deaths annually. HIV infected people were highly discriminated and neglected by nurses during their clinical practice due to the misconceptions and misbeliefs regarding HIV/AIDS. In future, nursing students have to work in hospitals and they have responsibility to provide quality care to the HIV infected patients. Therefore, there is a need to enhance the level of knowledge and attitude of the students regarding HIV/AIDS which is very important to eradicate discrimination and negligence of HIV/AIDS infected patients. A cross sectional study was carried out among all students at College of Nursing, Jaffna to assess the knowledge and attitude towards HIV/AIDS. The data were collected using an adapted self-administered questionnaire which consists of 25 questions to assess knowledge, and 15 questions to assess attitude. The data were analyzed using SPSS 21 statistical software. 92 students participated in this study. The results of the study revealed that 60.9% of students had good level of knowledge and 39.1% of students had adequate level of knowledge with the mean of 36.98 (SD+6.37). The positive and negative attitudes towards HIV/AIDS among participants were 96.7%, 3.3% respectively. This study concluded that students of College of Nursing had good knowledge and positive attitude on HIV/AIDS. Most of the students had good knowledge on HIV/AIDS, its mode of transmission, and prevention.
Keywords: Knowledge; Attitudes; HIV; Nursing